Consumption frequency of ultra‐processed foods and beverages among 6‐ to 36‐month‐olds in Kampala, Uganda - Catherine L. Mwesigwa; Sudeshni Naidoo (Maternal and Child Nutrition)
Abstract The nutrition transition in sub‐Saharan Africa has led to increased consumption of ultra‐processed foods in infancy, especially sweet foods. This has heightened the risk for nutrition‐related non‐communicable diseases, including dental caries and overweight/obesity, and promotes poor food choices later in life. The present study used a cross‐sectional design to investigate the consumption frequency of ultra‐processed foods and beverages among urban 6‐ to 36‐month‐olds attending four selected health facilities in Kampala using a standardised questionnaire and 24‐h diet recall record. The primary outcome was the consumption of at least one ultra‐processed food or beverage (UPFB) the previous day, and frequency of UPFB consumption of the week before was the secondary outcome. Four hundred and ten caregiver–child pairs were randomly recruited, 94% of caregivers being mothers with a mean age of 30.7 (±5.3) years. Fifty‐nine per cent of mothers and 73% of fathers had attained a college education. The median age of children was 18 months and 51% were female. Most children (57%) consumed at least one UPFB the previous day. In the week before, 69% had consumed UPFB frequently (4–7 days) which was significantly positively associated with maternal education (odds ratio [OR] = 2.85, 95% confidence interval [CI]: 1.02–7.96, p = 0.045) and child's age ([OR = 2.87, 95% CI: 1.62–5.08, p < 0.001], [OR = 3.68, 95% CI: 1.88–7.20, p < 0.001]). In conclusion, the dietary habits of the surveyed Ugandan population were unhealthy, characterised by the frequent consumption of UPFB with added sugar. There is an urgent need to re‐enforce existing Ugandan food regulation guidelines and policies and to build strong nutritional education programmes to enhance health‐promoting environments in early childhood.